Comparison of age-related changes in anti-Müllerian hormone levels and other ovarian reserve tests between healthy fertile and infertile population. (2nd July 2016) - Bozkurt, Banu; Erdem, Mehmet; Mutlu, Mehmet Firat; Erdem, Ahmet; Guler, Ismail; Mutlu, Ilknur; Oktem, Mesut
Abstract: In this study, we aimed to determine whether anti-Müllerian hormone (AMH) levels vary between fertile and infertile populations and compare them with basal follicle-stimulating hormone (FSH) levels and antral follicle count (AFC). This was a prospective study that included 177 primarily infertile patients who underwent IVF treatment and 162 healthy fertile patients admitted to our clinic for benign diseases. FSH and AMH levels and the AFC of the infertile and fertile populations were compared between the age categories <30, 30–39 and ≥40. Correlations between AMH, basal FSH, and AFC with age were evaluated. AFC and AMH levels did not differ between the fertile and infertile groups in all age categories. AMH was inversely correlated with age in both the fertile and infertile populations. However, AFC revealed a stronger correlation with age in both the fertile and infertile populations compared with basal FSH and AMH. Age was positively correlated with basal FSH and inversely correlated with AMH and AFC. In conclusion, there was no significant difference between the fertile and infertile populations in terms of AMH or AFC. The decrease in ovarian reserve in infertile patients is directly related to age, not infertility.